THE SUBTITLING APPLICATION ON TEACHING LITERARY WORKS USING AUDIO-VISUAL FOR THE DEAF AND HARD OF HEARING FIRST GRADE STUDENTS OF SLBN BOLON JUNIOR HIGH - Lilik Untari (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2011)
This research was aimed at seeking out the impacts of Subtitle for the Deaf and Hard of Hearing (SDH), Emotional Subtitle (ES), and Caption in the story comprehension capability of the first grade students at SLBN Bolon Colomadu upon the Naruto series episode 89. The research is experimental in which the total sampling is employed since there were three students only in the school. A level finder test was bestowed upon the three to ensure that they shared the same level on story comprehension. A capability test upon the story comprehension was executed to recognize the students’ comprehension on the story of Naruto. A questionnaire session was given to acknowledge the opinions of the students regarding with SDH, ES, and Caption. Analyzing the data, it was found out that SDH received 43.34% subjective positive view and 6.6% objective positive view, ES received 73% subjective positive view and 17% objective positive view, and Caption received 34% subjective positive view and 34% objective positive view. This result pointed out that Caption performed better than the other two because Caption sparked more objective positive view than the other two.